Towards selective laser paint stripping using shock waves produced by laser-plasma interaction for aeronautical applications on AA 2024 based substrates. (September 2021) - Ünaldi, Selen; Papadopoulos, Kosmas; Rondepierre, Alexandre; Rouchausse, Yann; Karanika, Alexandra; Deliane, Florent; Tserpes, Konstantinos; Floros, Giannis; Richaud, Emmanuel; Berthe, Laurent
Abstract: Laser stripping is a process which typically includes different forms of ablation phenomena. The presented work investigates a mechanical stripping process using high pressure laser-induced shock waves in a water confined regime. Power density is studied as a parameter for selective laser stripping on painted specimens and for adhesion relations with single layer epoxy targets. A flashlamp-pumped Nd:YAG laser with fixed spot size (4 mm) is shot on single layer epoxy and several layers of polymeric paint applied on a AA 2024-T3 (Aluminium) substrate. After laser treatment, samples are investigated with optical microscopy, profilometer and chemical analysis (FTIR & TGA). The results show that selective laser stripping is possible between different layers of external aircraft coatings and without any visual damage on the substrate material. In parallel to the experimental work, a numerical model has been developed to explain the background of the physical mechanisms and to qualitatively evaluate the detailed stress analysis and interfacial failure simulation for a single layer of epoxy on an aluminium substrate. The predicted failure patterns agree with the surfaces of the tested specimens observed by a microscope.